A SUCCESSION PLANNING MODEL FOR ACADEMIC HEADS - Gilbert S. Arrieta; Caridad N. Barrameda; I Ketut Sudarsana (Jurnal Penjaminan Mutu, 2022)
This study identified the practices, issues and concerns, and key elements of a succession planning model for academic heads for the five private sectarian schools in the Philippines. It was conducted in school year 2018-2019, and participated by fifty-eight (58) religious administrators and lay academic heads and teachers Using the key features of participatory method, workshops, focus group discussion, and interviews were conducted for data gathering. The results showed that the practices in the selection and appointment of academic heads were administration’s preference, and criteria for selection and appointment of academic heads. From these practices, the issues and concerns that emerged were objectivity of decision, professional growth, spirituality and culture, and motivation. The elements of succession planning which are vision-mission, spirituality and culture, institutional policies, processes, and procedures, and professional growth were identified based on the practices, and issues and concerns. From these data, the succession planning model for academic heads was developed. The steps in the succession planning are understand the school organizational culture, build a shared vision, set and implement policies and leadership standards, provide personal and moral development programs, provide leadership development programs, and select and appoint academic heads. All policies and programs of the succession planning model must be anchored on the vision-mission of the schools. The faith and spiritual development programs (for private sectarian schools) or the personal and moral development programs (non-sectarian and public schools) are important in the preparation and appointment of future academic heads.